Pengaruh Karakteristik Tujuan Anggaran Terhadap Kinerja Aparat Pemerintah Daerah Pada Satuan Kerja Perangkat Daerah Kabupaten Bantul - Sari, Deltania Lunar; Susliyanti, Eni Dwi (Universitas PGRI Yogyakarta, 2020)
The budgeting process is an important activity and involves various top-level managers as well as lower-level managers who play a role in preparing and evaluating alternatives to budget objectives, where budgets are always used as the best benchmarks of manager performance. This research was carried out at the Regional Device Work Unit (SKPD) Bantul District Special Province of Yogyakarta. This research is included in the type of applied research applied with the aim of applying, testing and evaluating the ability of a theory applied in solving practical problems. The nature of this research is included into quantitative and explanatory descriptive research.The results of this study indicate that budget participation, Â Budget feedback, Budget evaluation and The clarity of the budget objective have a positive effect on the performance of the local government officials of Bantul because it obtains a significance value of Î± <0.05.Based on the results of multiple regression analysis with a significance level of 5%, the results of this study conclude, simultaneously that budget participation has a positive effect on the performance of the local government.Â Keywords: Budget, Participation, Feedback, Evaluation and Objectives Clarity